The identity of Amplaria nazinta (Chamberlin, 1910): a century-old millipede mystery resolved (Diplopoda, Chordeumatida, Striariidae) - Shear, William A.; Nosler, Philip; Marek, Paul (Zootaxa, 2017)
Amplaria nazinta (Chamberlin, 1910) is redescribed from freshly collected male specimens and its identity as a species of Amplaria Chamberlin, 1941 is confirmed. We amend the diagnosis of Amplaria, and for the first time report the presence of a limbus in a chordeumatidan millipede.